Royal Bank of Scotland/Scottish Economic Society Seventh Annual Lecture: Making Britain More Competitive: A Critique of Regulation and Competition Policy. - Helm, D (2001)
The paper provides a critique of the Labour government's attempts to make Britain more competitive by reforming regulation and competition policy. It is argued that the Utilities Act (2000) has not reduced the cost of capital, but rather the discretionary powers of the regulators have been generalised further, augmented by government guidelines covering additional social and environmental objectives. The paper reviews the impact of the windfall tax, the use of private balance sheets as a private-sector borrowing requirement, and the growing costs of regulation. The Competition Act (1998) has concentrated on conduct rather than structure, and the paper argues that the neglect of structural change to create competition, rather than merely sustain it, reduces the scope for enhancing productivity and hence the competitive position of the economy.